Cognitive dysfunction mediates the effects of poor physical fitness on decreased functional independence in heart failure. Issue 2 (18th February 2014) - Alosco, Michael L; Spitznagel, Mary Beth; Sweet, Lawrence H; Josephson, Richard; Hughes, Joel; Gunstad, John
<x xml:space="preserve">Abstract</x> Aim Heart failure (HF) patients require assistance with activities of daily living (ADL). Poor physical fitness has recently been identified as a contributor to the high rates of disability in HF, though the mechanisms for such effects are unclear. Although not previously examined, decreased fitness might adversely impact ADL in HF through its known association with cognitive impairment, a key correlate of self‐care abilities in this population. We sought to test this possibility using a model‐based approach. Methods A total of 197 patients with HF completed a physical fitness test and a neuropsychological test battery. A total ADL composite was derived from the Lawton Brody scale. Structural equation modeling tested whether cognitive function mediated the association between physical fitness and total ADL. Results Fitness was reduced, and cognitive dysfunction and impaired ADL were prevalent. The initially significant association between fitness and total ADL was attenuated when cognitive function was introduced as a mediator. This model showed good fit (comparative fit index = 0.91: root mean‐square error of approximations = 0.077) with a significant indirect pathway between physical fitness and total ADL through cognitive function: Decreased physical fitness was associated with cognitive dysfunction (β = 0.35), which predicted greater assistance with ADL (β = 0.22). Conclusions Poor physical fitness might lead to decreased functional independence in HF through its negative effects on cognitive function. Prospective studies are required to confirm our findings, identify other mechanisms by which poor fitness impacts ADL, and examine whether exercise interventions can improve cognition and help preserve ADL independence in HF. Geriatr Gerontol Int 2015; 15: 174–181.